Frequency of Abnormally Low Neuropsychological Scores in Post-COVID-19 Syndrome: the Geneva COVID-COG Cohort. (9th August 2022) - Voruz, P; Jacot de Alcântara, I; Nuber-Champier, A; Cionca, A; Allali, G; Benzakour, L; Lalive, P H; Lövblad, K-O; Braillard, O; Nehme, M; Coen, M; Serratrice, J; et al.
Abstract: Objective: Several studies have reported poor long-term neuropsychological performances in patients following severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, but none has yet considered the effect of administering multiple intercorrelated neuropsychological tests and assessed the frequency of cognitive deficits in a normative population. Our aim was therefore to assess the presence of cumulative neuropsychological deficits in an actual post-coronavirus disease of 2019 (COVID-19) comparison group versus one simulated using Monte-Carlo methods. Method: Validated neuropsychological Monte-Carlo simulation methods were applied to scores from a battery of neuropsychological tests (memory, executive, attentional, perceptual, logical reasoning, language, and ideomotor praxis) administered to 121 patients who had had mild, moderate, or severe COVID-19 (mean age: 56.70 years; 32% women), 222 ± 43 days post-infection. The cumulative percentages of the three severity subgroups were compared with the results of a false discovery rate-corrected probability analysis based on normative data. Results: The cumulative percentages of deficits in memory and executive functions among the severe and moderate patients were significantly higher than those estimated for the normative population. Moderate patients also had significantly more deficits in perception and logical reasoning. In contrast, the mild group did not have significantly more cumulative deficits. Conclusions: Moderate and severe forms of COVID-19 cause greater long-term neuropsychological deficits than those that would be found in a normative population, reinforcing the hypothesis of long-term effects of SARS-CoV-2 on cognitive function, independent of the severity of the initial infection.